Transmission electron microscopy reveals distinct macrophage- and tick cell-specific morphological stages of Ehrlichia chaffeensis - Dedonder, Sarah E.; Cheng, Chuanmin; Willard, Lloyd H.; Boyle, Daniel L.; Ganta, Roman R. (My University, 2012)
Background: Ehrlichia chaffeensis is an emerging tick-borne rickettsial pathogen responsible for human monocytic ehrlichiosis. Despite the induction of an active host immune response, the pathogen has evolved to persist in its vertebrate and tick hosts. Understanding how the organism progresses in tick and vertebrate host cells is critical in identifying effective strategies to block the pathogen transmission. Our recent molecular and proteomic studies revealed differences in numerous expressed proteins of the organism during its growth in different host environments. Methodology/Principal Findings: Transmission electron microscopy analysis was performed to assess morphological changes in the bacterium within macrophages and tick cells. The stages of pathogen progression observed included the attachment of the organism to the host cells, its engulfment and replication within a morulae by binary fission and release of the organisms from infected host cells by complete host cell lysis or by exocytosis. E. chaffeensis grown in tick cells was highly pleomorphic and appears to replicate by both binary fission and filamentous type cell divisions. The presence of Ehrlichia-like inclusions was also observed within the nucleus of both macrophages and tick cells. This observation was confirmed by confocal microscopy and immunoblot analysis. Conclusions/Significance: Morphological differences in the pathogen’s progression, replication, and processing within macrophages and tick cells provide further evidence that E. chaffeensis employs unique host-cell specific strategies in support of adaptation to vertebrate and tick cell environments.
Keywords: Ehrlichia chaffeensis; Transmission electron microscopy; Tick cells; Macrophage; Human monocytic ehrlichiosis; Rickettsial pathogens